Sharia Economic Law Criticism on Muhammad Syahrûr’s Hudûd Theory Regarding Bank Interes - Eka Rahayu, Annisa; Kamaludin Yusup, Deni; Athoillah, Mohamad Anton; Hakim, Sofyan Al (UPT Publikasi Ilmiah UNISBA, 2024)
n modern economics applied by conventional financial institutions, the interest system is inseparable. Economic system based on sharia principles emerged as a solution to riba-based (usury-based) transactional activities, which in sharia economic law is in the khilafiyyah (dissent) territory amongst scholars regarding whether the conventional bank interest is riba which is prohibited by Islamic law. A figure named Muhammad Syahrûr came up and offered his theory of limits (nazhariyyah al-hudûd) in providing riba limitations in the Quran. This research aims to describe M. Syahrûr's thoughts on bank interest based on his theory of limits, and to analyze it based on the review of sharia economic law (fiqh muamalah mâliyyah). this reseach is understood as a literary study research which is a research on secondary materials. The type of data used in this research is secondary data, which is literature focusing on the thoughts of a figure, which is Muhammad Syahrûr.The result of the research shows that Muhammad Syahrûr's opininion that allows the practice of bank interest based on his theory of limits (nazhariyyah al-hudûd) is a marjûh (weak) opinion, since it is not supported by valid arguments and it also contradicts the opinions of the jumhur ulama (the majority of the scholars).